Seed targeting with tiny anti-miR-1297 inhibits EMT in melanoma cells. (2nd January 2019) - Han, Y.; Li, X.; Ma, C.; Ji, X.; Li, T.; Zheng, X.; Zhang, J.; Yan, J.; Zhang, D.; Bai, J.
Abstract: MicroRNAs (miRNAs) are small, noncoding RNAs that have tissue- and cell-specific expression. They have the ability to regulate the malignant proliferation and transformation of tumour cells. The research focussed on the expression and role of miR-1297 in melanoma. We firstly found that miR-1297 is up-regulated in melanoma tissues and cell lines. Functionally, phosphatase and tension homology deleted on chromsome ten gene (PTEN) was used as a potential target for miR-1297 and detected using Western blotting and immunohistochemistry (IHC). We then used chemical synthesis of anti-miR1297 to explore the influence on melanoma cells and examined the effects on A375 cell proliferation using MTT and western blotting methods. The results showed that anti-miR-1297 transfected A375 cells could inhibit the growth. Furthermore, transfection with anti-miR-1297 reduced PTEN protein expression and partially restrained A375 cells proliferation, migration and reversed Epithelial–Mesenchymal Transition (EMT) progression. In conclusion, we tentatively put forward that miR-1297 might be the key oncomiR in melanoma, and seed-targeted anti-miR-1297 might serve as a new tactic for miR-1297-based therapies.